Mixing of Isaria fumosorosea with enhanced diatomaceous earth and bitterbarkomycin for control of Rhyzopertha dominica. Issue 4 (3rd July 2013) - Riasat, Tahira; Wakil, Waqas; Yasin, Muhammad; Kwon, Yong Jung
Abstract: The virulence of Isaria fumosorosea alone and integrated with an enhanced formulation of diatomaceous earth (diatomaceous earth + bitterbarkomycin, DEBBM) was tested against the lesser grain borer Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) under laboratory conditions on stored wheat. The fungus was applied to wheat grains at various concentrations of 3.60 × 10 6, 3.60 × 10 8, and 3.60 × 10 10  conidia/kg alone, or in combination with 15 and 30 ppm of DEBBM. R. dominica was held at 20, 25 and 30°C and two RH regimes (56 and 75%) and mortality was registered after 5, 10 and 15 d. Generally, I. fumosorosea was most effective at 25°C caused the highest mortality of R. dominica at 56% RH. The increase of temperature, concentration and exposure interval increased the insecticidal effect of DEBBM at low RH level. The DE alone suppressed the progeny emergence at higher dose rate as compared I. fumosorosea alone, but their simultaneous use further reduced the progeny production of R. dominica . The integrated use of both tested bio control agents synergized the effect of each other and caused the highest mortality at 25°C and 56% RH. The results clearly demonstrated that I. fumosorosea and new enhanced DEBBM can be integrated to be an effective control measure for R. dominica in stored wheat.